Continuous Monitoring and Characterization of Copolymerization Reactions of Acrylate Monomers with Indistinguishable Ultraviolet Spectra Using Infrared Spectroscopy. Issue 6 (12th July 2022) - Siqueira, Julia S.; Reed, Wayne F.
Abstract: Applications of Automatic Continuous Online Monitoring of Polymerization reactions (ACOMP) have steadily expanded over the past 20 years. An ultraviolet (UV) detector, often combined with a differential refractive index detector (RID), is the usual method to track monomer conversion, but the method can fail when comonomers have similar UV spectra. Here, Fourier‐transform infrared spectroscopy (FTIR) is coupled to ACOMP to separate comonomer conversion during solution copolymerization of tert‐butyl acrylate (tBA) and n‐butyl acrylate (nBA). The UV spectra of these comonomers are too similar for separation. The FTIR region between 1100 and 1410 cm −1, however, shows a strong difference between tBA and nBA peaks—1403 and 1192 cm −1, respectively. Reaction rates determined from FTIR data show that tBA's is higher than nBA's. The terpolymerization of tBA, nBA, and methyl methacrylate (MMA) is also monitored, using MMA's 1325 cm −1 peak. Reaction rates are significantly lower than in the nBA/tBA copolymerization. The incorporation of FTIR into ACOMP opens the path for further expansion to a wide variety of copolymerization reactions, including systems of three or more comonomers. It can be a key new detector in the next steps for development of fully automatic feedback control of composition and molecular weight. Abstract : Decoupling of acrylate comonomer signals during copolymerization using only ultraviolet spectroscopy (UV) is a very hard task. In this work, Fourier‐transform infrared spectroscopy (FTIR) is successfully employed for the continuous monitoring and characterization of an isomeric butyl acrylate pair ( tert ‐ and n ‐). This progress paves the way for online real‐time tracking of individual monomers in multicomponent polymerization reactions.